Intractable Persistent Direction-Changing Geotropic Nystagmus Improved by Lateral Semicircular Canal Plugging - Toru Seo; Kazuya Saito; Katsumi Doi (Case Reports in Otolaryngology)
Antigravitational deviation of the cupula of the lateral semicircular canal, which is also called light cupula, evokes persistent direction-changing geotropic nystagmus with a neutral point. No intractable cases of this condition have been reported. In our case, a 67-year-old man complained of positional vertigo 3 months after developing idiopathic sudden hearing loss in the right ear with vertigo. He showed a persistent direction-changing geotropic nystagmus with a leftward beating nystagmus in the supine position. The nystagmus resolved when his head was turned approximately 30° to the right. He was diagnosed with light cupula of the right lateral semicircular canal and was subsequently treated with an antivertiginous agent. However, his symptoms and positional nystagmus did not improve, so the right lateral semicircular canal was plugged by surgery. One month after surgery, his positional vertigo and nystagmus were completely resolved. We speculated that the cause of the patient’s intractable light cupula was an enlarged cupula caused by his idiopathic sudden hearing loss.